1992
DOI: 10.1111/j.1751-1097.1992.tb04231.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological Properties of Some Benzopsoralen Derivatives

Abstract: The biological activity of some benzopsoralen derivatives, prepared with the aim of obtaining new drugs for photochemotherapy, has been studied. The more interesting compounds are 4-hydroxymethyl-4',5'-benzopsoralen and 4-hydroxymethyl-4',5'-tetrahydro-benzopsoralen, which were found to be active in the dark also: DNA and RNA synthesis were both inhibited in Ehrlich cells, even if in a partially reversible fashion, while protein synthesis remained unaffected. In Chinese hamster ovary cells cultured in vitro, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

1993
1993
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Both mono-and diadducts are effective in inhibiting DNA synthesis, although decreased photoinduced mutagenicity has been found in the case of monofunctional as opposed to bifunctional furocoumarins [7]. For this reason monofunctional furocoumarins have been prepared and investigated by several groups [2,[8][9][10][11][12] with the aim of reducing these undesired side effects. It has also been shown that the reactivity of the double bonds can be modified by substitution with methyl groups, thus influencing charge donation, steric effects and the lipophilic nature of the furocoumarins [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both mono-and diadducts are effective in inhibiting DNA synthesis, although decreased photoinduced mutagenicity has been found in the case of monofunctional as opposed to bifunctional furocoumarins [7]. For this reason monofunctional furocoumarins have been prepared and investigated by several groups [2,[8][9][10][11][12] with the aim of reducing these undesired side effects. It has also been shown that the reactivity of the double bonds can be modified by substitution with methyl groups, thus influencing charge donation, steric effects and the lipophilic nature of the furocoumarins [13].…”
Section: Introductionmentioning
confidence: 99%
“…Furocoumarins also react with proteins and membrane lipids, either by direct photoaddition or by generation of singlet oxygen, which suggests that parallel to the DNA reaction other cellular targets should be taken into account when attempting to explain furocoumarin photosensitization [14]. This method has been used by several groups for measuring the generation of singlet oxygen [6,10,[15][16][17][18][19]. The author was interested in the preparation and investigation of furocoumarins which have hydrophobic and bulky substituents on the furan moiety, in order to check the influence of the structural changes in position 3 of the furocoumarin skeleton on the interaction with DNA as well as on the absorption and fluorescence spectra, the lipophilicity, and the photobleaching effect of N,N-dimethyl-p-nitrosoaniline.…”
Section: Introductionmentioning
confidence: 99%
“…Benzopsoralen derivatives represent an interesting approach in the research of less toxic compounds to be used in photochemotherapy. They present an antiproliferative activity even in the dark (Bordin et al 1992). Since one of the reactive site of psoralen structure (3, 4 double bond) is blocked by the introduction of a benzenic or cyclohexenilic ring, Phese compounds are usually not able to form biadducts with DNA or are very weak cross-linking agents, respectively (Palumbo e f al.…”
mentioning
confidence: 99%
“…Among these compounds the 4-hydroxymethyl derivatives of benzo-and tetrahydrobenzo-psoralen appear very interesting. In fact, they effectively inhibit DNA and RNA synthesis in Ehrlich cells in the dark and by UVA irradiation, although they are unable to induce erythemas on guinea-pig skin in vivo (Bordin et al 1992).…”
mentioning
confidence: 99%
“…Thus, with the aim to obtain furocoumarins having a reduced toxicity, various authors prepared and studied several monofunctional derivatives, incapable of forming ISC. A monofunctional furocoumarin can be obtained by several ways: blocking one of its two photoreactive sites by insertion of a suitable group, as for 3-carbethoxypsoralen [15], or by cumulating a fourth nucleus, e.g., the pyridopsoralens having a pyridine condensed at 3,4 positions [16] and benzopsoralens in which the fourth nucleus is a benzenic one at 4 , 5 position [17]. We also studied several new angelicin derivatives, which, for the geometric parameters of their angular molecular structure, can hardly induce ISC [18].…”
Section: Introductionmentioning
confidence: 99%